Prolonged Detection of Zika Virus Nucleic Acid Among Symptomatic Pregnant Women: A Cohort Study. (9th March 2018) - Lozier, Matthew J; Rosenberg, Eli S; Doyle, Kate; Adams, Laura; Klein, Liore; Muñoz-Jordan, Jorge; Alvarado, Luisa I; Sharp, Tyler M; Paz-Bailey, Gabriela
Abstract: A prospective cohort of women with reverse transcription polymerase chain reaction (RT-PCR) confirmed Zika virus infection aged 18–39 years in Puerto Rico found that pregnant women have about a 3-fold longer estimated median detection of Zika virus RNA in serum, which can increase definitive diagnosis of infection and facilitate timely and appropriate clinical management.